Quitting time: When do honey bee foragers decide to stop foraging on natural resources? - Rivera, Michael D.; Donaldson-Matasci, Matina; Dornhaus, Anna (Frontiers in Ecology and Evolution, 2015)
Honey bee foragers may use both personal and social information when making decisions about when to visit resources. In particular, foragers may stop foraging at resources when their own experience indicates declining resource quality, or when social information, namely the delay to being able to unload nectar to receiver bees, indicates that the colony has little need for the particular resource being collected. Here we test the relative importance of these two factors in a natural setting, where colonies are using many dynamically changing resources. We recorded detailed foraging histories of individually marked bees, and identified when they appeared to abandon any resources (such as flower patches) that they had previously been collecting from consistently. As in previous studies, we recorded duration of trophallaxis events (unloading nectar to receiver bees) as a proxy for resource quality and the delays before returning foragers started trophallaxis as a proxy for social need for the resource. If these proxy measures accurately reflect changes in resource quality and social need, they should predict whether bees continue foraging or not. However, neither factor predicted when individuals stopped foraging on a particular resource, nor did they explain changes in colony-level foraging activity. This may indicate that other, as yet unstudied processes also affect individual decisions to abandon particular resources.